Fishing efficiency of biodegradable PBSAT gillnets and conventional nylon gillnets used in Norwegian cod (Gadus morhua) and saithe (Pollachius virens) fisheries - Grimaldo, Eduardo; Herrmann, Bent; Vollstad, Jørgen; Su, Biao; Føre, Heidi Moe; Larsen, Roger B.; Tatone, Ivan (ICES Journal of Marine Science, 2018)
This is a pre-copyedited, author-produced version of an article accepted for publication in ICES Journal of Marine Science following peer review. The version of record Grimaldo, E., Herrmann, B., Vollstad, J., Su, B., Føre, H.M., Larsen, R.B. & Tatone, I. (2018). Fishing efficiency of biodegradable PBSAT gillnets and conventional nylon gillnets used in Norwegian cod ( Gadus morhua )and saithe ( Pollachius virens ) fisheries. ICES Journal of Marine Science, 75 (6), 2245–2256, is available online at: https://doi.org/10.1093/icesjms/fsy108 . Fishing trials were carried out to compare the relative fishing efficiency of gillnets made of a new biodegradable resin (polybutylene succinate co-adipate-co-terephthalate, PBSAT) with conventional (nylon) nets. The fishing trials covered two consecutive fishing seasons (2016 and 2017) for cod ( Gadus morhua ) and saithe ( Pollachius virens ) in northern Norway. Results generally showed better catch rates for the nylon gillnets. The biodegradable PBSAT gillnets caught 50.0% and 26.6% fewer cod, and 41.0% and 22.5% fewer saithe than the nylon gillnets in 2016 and 2017, respectively. Even though the relative catch efficiency of the biodegradable gillnets was slightly better in 2017 than in 2016, the difference with respect to the catch efficiency of nylon gillnets may be too large for biodegradable gillnets to be accepted by fishermen if they were available commercially. Tensile strength measurements of the nylon and biodegradable PBSAT gillnets carried out before and after the fishing trials showed that the both types of gillnets had significant reductions in tensile strength and elongation at break, especially in 2017. Although less catch efficient than nylon gillnets, biodegradable PBSAT gillnets show great potential for reducing ghost fishing and plastic pollution at sea, which are major problems in these fisheries.